Lost Surveillance Studies. A Critical Review of French Work on CCTV - Klauser, Francisco (My University, 2009)
The paper engages with ‘lost’ CCTV studies in French academia. It discusses three specificities of the French CCTV context – the legal regulation of CCTV, the journal En toute sécurité, and the quasi absence of publicly mandated evaluations of CCTV systems – thus studying how they are reflected in the existing CCTV literature. This approach provides an exploratory framework for investigating the key elements that French CCTV studies add to the Anglophone literature, and for examining the knowledge generation in Surveillance Studies.